Quality Measurement as a Path to High Quality Care; Comment on “Quality and Performance Measurement in Primary Diabetes Care: A Qualitative Study in Urban China” - John C. Matulis III; Rozalina G. McCoy (International Journal of Health Policy and Management, 2023)
A rigorous evaluation of the implementation of a diabetes quality measure implementation program across community healthcare clinics in Shanghai, China, where both quality measurement and primary care delivery are relatively recent but centrally supported, identified important concerns about the meaningfulness, feasibility, and accuracy of quality measures that are relevant to all quality measurement programs. These include the importance of stakeholder involvement in measure development and implementation, the need to select measures that accurately and reliably reflect care quality, the link between incentives for improved performance and data manipulation, the necessity for scientific credibility and practical feasibility of the measure, and the assurance that measure performance can be impacted by those being evaluated. In addition to elaborating on these aspects of quality measurement, we also discuss the need for quality measures that are balanced across established domains of quality, are not burdensome to participants, and are transparent, parsimonious, nimble, and oriented around continuous evaluation and improvement.